2010
DOI: 10.1002/app.31897
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic modification of dickite and salt spray test study on LLDPE/modified dickite composite

Abstract: Dickite particles were modified by silane coupling agent, hexadecyl phosphate, oleic acid, and stearic acid (SA), respectively. Modified dickite was composed with linear low-density polyethylene (LLDPE) to prepare a series of LLDPE/modified dickite composites. Hydrophilicity of modified dickite was characterized by dispersion experiments and contact angle tests. The results indicated that hydrophilicity of modified dickite decreases sharply, compared with nonmodified dickite. Among four modifying agents, SA ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Nonexfoliated dickite aggregates and intercalated thin tactoids are prone to parallel to the nanocomposite surface. This observation is similar to the case of dickite/LLDPE microcomposite we prepared previously . Bigger layered particles in composite are prone to be oriented at the process of hot press formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonexfoliated dickite aggregates and intercalated thin tactoids are prone to parallel to the nanocomposite surface. This observation is similar to the case of dickite/LLDPE microcomposite we prepared previously . Bigger layered particles in composite are prone to be oriented at the process of hot press formation.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, it has been pointed out that the properties of polymer/clay nanocomposites also depend on the type of used clay . In our previous study, we found that another clay dickite was also an excellent filler to prepare polymer/clay composites . The experiment results revealed that the resulting dickite/ linear low‐density polyethylene (LLDPE) nanocomposites also possessed better barrier properties.…”
Section: Introductionmentioning
confidence: 99%
“…The cracks are conducive to the penetration of flame and combustible gas, and CO and CO 2 generated by combustible decomposition are also easy to diffuse outward through the cracks. 37 Therefore, although the addition of MHPA can play a role in flame retardancy, there are still defects that make the improvement of flame retardancy limited. To improve this situation, the introduction of MH will play a positive role.…”
Section: Combustion Behaviors Of Hdpe and Its Compositesmentioning
confidence: 99%
“…Therefore, the intensity of the 3450 cm À1 band related to the adsorbed water was increased. After organic modification, the FTIR spectra of O-D and OA-D showed the asymmetric and symmetric CH 2 stretching at 2925 and 2852 cm À1 , 18 indicating that the MPS modifier was grafted onto the surface of diatomite. Fig.…”
Section: Characterization Of Diatomitementioning
confidence: 99%